ANALISIS FAKTOR FAKTOR PENYEBAB TIMBULNYA PERILAKU BULLYING PADA PESERTA DIDIK - Nadya; Dessy Wardiah; Farizal Imansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This researcher examines family factors, peer factors, and media factors as causes of bullying in students of State Elementary School 42 Palembang. The aim is to determine the extent to which family factors, peer factors, and media factors cause bullying behavior in students. The benefits of this study are to help schools in overcoming cases of bullying that occur in students in terms of the causal factors. The research method uses a qualitative method, and the type of research used is a case study. The researcher collected data using interview, observation and documentation techniques. The informants were students who had been perpetrators of bullying, the principal, guidance and counseling teachers, and homeroom teachers. The results of the study showed that: (1) family factors are the cause of bullying behavior in students, because the family is less harmonious, not intact (parents died or divorced), the socialization process is not perfect from their families, communication is not smooth between parents and children. (2) peer factors are the cause of bullying behavior in students, because the high intensity of communication between peers allows these students to be incited by their friends who are negatively oriented. (3) media factors are the cause of bullying behavior in students, due to the misuse of social media as a medium for bullying.